Analytic Presentation of Frequency Dependence of Q-Factor for Planar Inductors on Different Substrates - Jankovskis, J.; Yurshevich, V.; Rankis, G. (Elektronika ir Elektrotechnika, 1999)
The modelling of frequency dependence of quality factor Q for planar inductors is based on the use of two-pole equivalent circuit with elements that account for losses both in conductor and in substrate (dielectric and eddy current ones) of a coil, as well as self-capacitance. Two analytic presentations of Q-factor are derived: one with account of pronounced skin effect, another - without it. Experimental data reveal that as a rule more appropriate is the second one.